Structure elucidation of β-cyclodextrin–xylazine complex by a combination of quantitative 1H–1H ROESY and molecular dynamics studies - Ali, Syed Mashhood; Fatma, Kehkeshan; Dhokale, Snehal (Beilstein Journal of Organic Chemistry, 2013)
The complexation of xylazine with β-cyclodextrin was studied in aqueous medium. 1H NMR titrations confirmed the formation of a 1:1 inclusion complex. A ROESY spectrum was recorded with long mixing time which contained TOCSY artifacts. It only confirmed the presence of xylazine aromatic ring in the β-cyclodextrin cavity. No information regarding the mode of penetration, from the wide or narrow side, could be obtained. We calculated the peak intensity ratio from the inter-proton distances for the most stable conformations obtained by molecular dynamics studies in vacuum. The results show that highly accurate structural information can be deduced efficiently by the combined use of quantitative ROESY and molecular dynamics analysis. On the other hand, a ROESY spectrum with no spin diffusion can only compliment an averaged ensemble conformation obtained by molecular dynamics which is generally considered ambiguous.
Keywords: β-cyclodextrin; inclusion complex; ROESY; simulation studies; xylazine